Jezik, kulturni elementi in nabori znakov za Internetove uporabnike - Močilar, Franci (Uporabna informatika (Ljubljana), 1996)
People want communication and they need it. Internet makes it possible, still it is necessary to approach it to the end user. It would be ideal to communicate with the others in your own language. A lot will be done if the input of the main computer commands in native language will be anabled, if thecharacters on the screen will be comprehensible (the right character set will be chosen) and if the culture specific characteristics (date, time and numeric formatting, measurement system) will be presented in a comprehensible way. On practical basis the transparent language processing (LTP) model has been developed. It solves the problems of different languages, the confusion of different character sets and code sets, table conversions, transliteration, internationalization. The last level of the model should enable machine translation, on basis of language anlysis.
Keywords: Internet; kodne tabele; komunikacijski jeziki; mednarodni projekti; nabori znakov; standardizacija; strojno prevajanje; transliteracija